PHENANTHRENES AND BIBENZYLS FROM THE STEMS OF DENDROBIUM SONIA ‘RED JO’ AND THEIR ANTI-INFLAMMATORY ACTIVITY - Rayanil, Kanok-on; Sutassanawichanna, Wirunya; Jantham, Jintana; Jitkaroon, Watcharapa; Obsuwan, Kullanart; Sanongkiet, Sucharat Sanongkiet1 (Srinakharinwirot University Journal of Sciences and Technology, 2022)
Dendrobium orchids are one of the important economic crops in Thailand and most of them are used as cut flowers or ornamental plants. Several Dendrobium species have been utilized as folk medicines since ancient times in Asian countries for treatments of gastric disorders, fever, diabetes and for tonic purposes. However, the pharmacological applications of Thai Dendrobium orchids have not been reported. The aims of this study are to investigate the chemical constituents from Dendrobium Sonia ‘Jo Daeng’ (Orchidaceae) and to evaluate the anti-inflammatory properties of the isolated compounds in order to promote Thai Dendrobium orchids with valued-added medical features. As a result, the isolation of the ethyl acetate fraction from the stems of D. Sonia ‘Jo Daeng’ by using repeated chromatography techniques provided five stilbenoid derivatives including three phenanthrenes: nudol (1), confusarin (2) and lusianthridin (3), and two bibenzyls: gigantol (4) and tristin (5). Their structures were determined on the basis of MS and NMR spectroscopic data. The isolated compounds (1-5) were evaluated for their anti-inflammatory effects by inhibiting nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophage cells. Among these, confusarin (2) and gigantol (4) were found to exhibit promising anti-inflammatory activity with 79.42% and 71.57% inhibition, respectively, at 5 µg/mL without cytotoxicity. Therefore, this study supports the possibility of using D. Sonia ‘Jo Daeng’ as an anti-inflammatory inhibitor source.